1993
DOI: 10.1038/jcbfm.1993.9
|View full text |Cite
|
Sign up to set email alerts
|

Possible Origins and Distribution of Immunoreactive Nitric Oxide Synthase-Containing Nerve Fibers in Cerebral Arteries

Abstract: The distribution of perivascular nerve fibers expressing nitric oxide synthase (NOS)-immunoreactivity was examined in Sprague-Dawley and Long-Evans rats using affinity-purified rabbit antisera raised against NOS from rat cerebellum. NOS immunoreactivity was expressed within the endothelium and adventitial nerve fibers in both rat strains. Labeled axons were abundant and dense in the proximal anterior and middle cerebral arteries, but were less numerous in the caudal circle of Willis and in small pial arteries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
3
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(185 citation statements)
references
References 27 publications
10
169
3
3
Order By: Relevance
“…Therefore, NO, a basic mediator of vasodilation, is likely to be involved in cSCS-induced cerebral vasodilation. However this study did not determine whether NO synthase was from endothelial NOS, or the neuronal NOS that likely comes from nonadrenergic-noncholinergic nerve fibers (Nozaki et al, 1993). CGRP is another vasodilator that potentially contributes to cerebral vasodilation produced by cSCS in the same way that it contributes to SCS-induced vasodilation in the limbs .…”
Section: Neurohumoral Mechanisms-mentioning
confidence: 86%
“…Therefore, NO, a basic mediator of vasodilation, is likely to be involved in cSCS-induced cerebral vasodilation. However this study did not determine whether NO synthase was from endothelial NOS, or the neuronal NOS that likely comes from nonadrenergic-noncholinergic nerve fibers (Nozaki et al, 1993). CGRP is another vasodilator that potentially contributes to cerebral vasodilation produced by cSCS in the same way that it contributes to SCS-induced vasodilation in the limbs .…”
Section: Neurohumoral Mechanisms-mentioning
confidence: 86%
“…There has been little evidence to show how the nitroxidergic parasympathetic influence on cerebral blood vessels may participate in physiological processes in the whole animal although its having been found in so many vertebrate species (Goadsby, P. J. et al, 1996;Kimura, T. et al, 1997;Nozaki, K. et al, 1993;Toda, N. et al, 2000b;Yu, J. G. et al, 1997) certainly suggests that it might serve an important role. In fact, some reports have suggested both pathophysiologic as well as physiologic involvement of the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Histochemistry has showed that nitric oxide synthase (NOS)-containing nerves originating from the pterygoparatine ganglion (PPG) innervate arteries irrigating the cerebrum in many species. [3][4][5][6] We have reported that electrical stimulation of the unilateral PPG or the greater petrosal nerve (GPN), a preganglionic parasympathetic nerve that synaptically connects to the PPG, dilates the ipsilateral anterior cerebral artery (ACA), and the middle cerebral artery (MCA) in anesthetized monkeys 7 and dogs. 8 We have also found that these dilatations are suppressed by a NOS inhibitor.…”
Section: Introductionmentioning
confidence: 99%